1984
DOI: 10.1161/01.atv.4.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of low density lipoproteins during inhibition of cholesterol absorption by neomycin.

Abstract: The mechanisms for the hypocholesterolemic action of neomycin were examined in six patients with various levels of plasma total cholesterol and triglycerides. All patients were studied on a metabolic ward. The first period of 6 weeks was for control. Thereafter, neomycin (1.5 g/day) was started, and the patients were readmitted for another 6-week period after 2 to 3 months of treatment with the drug. Cholesterol balance studies showed that neomycin increased fecal excretion of neutral steroids by an average of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Hypolipidaemic therapy with cholesterol malabsorption by ketoconazole [22], neomycin [45] or sitostanol ester in the present study decreases TR, less so fractional catabolism for LDL apo B. The main reduction of LDL cholesterol, apo B and TR occurred in the dense LDL fraction with no compositional change, while the very dense fraction became apo B enriched.…”
Section: Discussionmentioning
confidence: 47%
“…Hypolipidaemic therapy with cholesterol malabsorption by ketoconazole [22], neomycin [45] or sitostanol ester in the present study decreases TR, less so fractional catabolism for LDL apo B. The main reduction of LDL cholesterol, apo B and TR occurred in the dense LDL fraction with no compositional change, while the very dense fraction became apo B enriched.…”
Section: Discussionmentioning
confidence: 47%
“…Previous human studies have found a positive association between increased LDL PR and increased cholesterol absorption. 20,21 It is possible, therefore, that increased LDL PR as a result of alcohol in the rabbit might be caused by increased cholesterol absorption. However, our work does not distinguish between this possibility and a direct effect of alcohol on lipoprotein metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Probucol and neomycin are each known to reduce both LDL and HDL,28 29 but the decrease in HDL cholesterol was not seen in patients taking cholestyramine alone. The major effect of lipid lowering treatment overall was to decrease LDL cholesterol by 18%, which resulted in a significant increase in the HDL ratio.…”
Section: Discussionmentioning
confidence: 99%